MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS MELALUI MODEL GENERATIVE MULTI-REPRESENTATION LEARNING - Dyah Ayu Maharani; Gusni Satriawati; Eva Musyrifah (ALGORITMA: Journal of Mathematics Education, 2020)
The ability to think creatively is a characteristic of 21st century learning. It takes learning innovation to accommodate increased creative thinking in learning materials. One alternative learning model that is thought to improve creative thinking is the Generative Multi-Representation Learning (GMRL) model. This study aims to analyze the effect of the GMRL model on mathematical creative thinking skills. The research was conducted in class X IPA at a public high school in Tangerang Regency. The method used was a quasi-experimental design with a post-test only randomize control group. The research sample was 66 students, 33 as the experimental group and 33 as the control group. Determination of the sample using cluster random sampling technique. Data collection on mathematical creative thinking skills using test instruments. In general, the research findings reveal that students' mathematical creative thinking skills taught using the GMRL model are higher than the conventional model. These skills include fluency, flexibility, originality and elaboration. The fluency indicator is more dominant than the other three indicators. The conclusion of this study is that the GMRL model is more effective in increasing mathematical creative thinking skills than the conventional model.